Provenance of heavy minerals from recent sediments of Balakyan River, Kurdistan Region, Iraq - Tobia, Faraj H.; Kafy, Rand H. (Sulaimani Journal for Pure and Applied Sciences, 2016)
Heavy mineral assemblages of the sediments in Balakyan River have been studied to determine their concentrations and provenance. Twelve sediment samples were analyzed for heavy mineral assemblage determination. The unstable heavy minerals (pyroxene and amphibole) represent more than 50%. The mineral chemistry and petrographic studies refer to the predominant clinopyroxene mineral is diopside. Actinolite, tremolite, and magnesiohornblende are common calc-amphibole in the sediments. The ultrastable heavy minerals are present in trace amounts. According to the mineral chemistry the clinopyroxene is derived from basic igneous rocks crystallized at 1150-1220⁰C and low pressure. Amphibole and epidote crystallized under low temperature and/or formed under low grade metamorphism. The detrital chromian spinel is derived from basic and ultrabasic igneous rocks of Alpine type peridotite formed in fore-arc. The probable source of these assemblages is Ophiolite Complex to the north of the studied area (north Iraq) and igneous parts of Walash Series and Red Bed Series also the sedimentary rocks of Shiranish and Tanjero formations.
Keywords: Heavy minerals; Balakyan River; Walash Series; Peridotite